Potentially inappropriate use of benzodiazepines and z-drugs in the older population—analysis of associations between long-term use and patient-related factors - Aliaksandra Mokhar; Niklas Tillenburg; Jörg Dirmaier; Silke Kuhn; Martin Härter; Uwe Verthein (PeerJ, 2018)
Introduction The long-term use of benzodiazepines (BZD) and z-drugs in older populations is associated with a variety of sociodemographic and health-related factors. Recent studies reported that long-term BZD and z-drugs use is associated with increased age, female sex, and severe negative psychological (e.g., depression) and somatic (e.g., chronic disease) factors. The current study explores the sociodemographic and health-related factors associated with long-term BZD and z-drugs use in the elderly. Methods We conducted a cross-sectional survey among randomly selected patients of one health insurance plan (“AOK North-West”) with BZD and z-drugs prescriptions in the past 12 months. The sample was stratified by appropriate German prescription guidelines (yes vs. no) and age (50–65 vs. >65 years). To examine the association of selected sociodemographic and psychological variables (e.g., sex, employment status, quality of life, depression) with long-term use, a binary logistic regression analysis was conducted. Results In total, data from 340 patients were analyzed. The mean age was 72.1 (SD = 14.5) years, and the most commonly used substances were zopiclon (38.1%), oxazepam (18.1%), and lorazepam (13.8%). The mean defined daily dose (DDD) was 0.73 (SD = 0.47). Insomnia was the main reason for prescribing BZD and z-drugs. The long-term use of BZD and z-drugs was significantly associated with unemployment (OR = 2.9, 95% CI [1.2–7.1]) and generally problematic medication use (OR = 0.5, 95% CI [0.2–1.0]). Discussion Unemployment status and problematic medication use had a significant association with the patient-reported, long-term use of BZD and z-drugs. Divergent prescription patterns might suggest problematic patterns of BZD and z-drugs use. The causal connection between the identified factors and problematic BZD and z-drugs prescription is not discussed in this paper. Nevertheless, employment status and possible evidence of general problematic drug use may be a warning signal to the prescribers of BZD and z-drugs.